Punishment and Reward: Does It Affect Employee Performance? - Hustia, Anggreany; Rahmawati, Desi (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Companies often ignore punishment and rewards for their employees because they consider this difficult to implement. This research aims to determine the effect of punishment and rewards on employee performance. Data was collected by questionnaires to employees of IBM company as a samples. The research analysis technique uses multiple regression, simultaneously test, partial tests and determination tests. The results of the research show that there is a positive influence of punishment and reward on employee performance. The F test is shows that there is a significant influence about the topic. This is supported by the determination test, which shows that punishment and reward make a good contribution to employee performance. The partial test are show punishment or reward have a significant effect on performance. It can be concluded the company must pay attention and provide appropriate policies on this matter so that the company's goals are achieved.